Sequencing and phylogenetic analysis of partial S1 genes of avian orthoreovirus isolates in Shandong province during 2015–2017 - Chen, Hao (Poult Sci, 2020)
Outbreaks of avian orthoreovirus (ARV) infection with primary symptoms of arthritis/tenosynovitis syndrome have been occurring more frequently in broiler flocks in China in recent years. This study aimed to investigate the genetic characteristics of ARV field strains in broiler flocks exhibiting arthritis/tenosynovitis syndrome from 9 cities in Shandong province during 2015 to 2017. A total of 64 synovial and tendon samples were obtained from broilers with significant arthritis/tenosynovitis syndrome, and 21 ARV field strains were obtained. Phylogenetic analysis of the σC nt/aa sequences revealed that only 4 isolates were clustered in genotype I, including vaccine strains S1133, 1733, and most of the ARV field strains identified previously in China. Eleven and 6 ARV field isolates were identified in genotypes II and V, sharing 70.9 to 76.0% and 53.0 to 55.2% nt identities with the vaccine strains, respectively. Previous studies in China have not reported these 2 serotypes of field strains, and prevalence of these ARV variants may be increasing in Chinese broiler flocks. Results of this study suggest that large-scale investigation of epidemic ARV should be conducted to explore the genetic diversity of ARV field isolates in China.